Research on the measurement and influencing factors of carbon emission efficiency in China’s transportation sector based on EBM-Tobit model - Song, Weifang; Zhang, Hao (Frontiers in Environmental Science, 2025)
The international community has increasingly focused on reducing carbon emissions. The transportation sector is one of the key areas of carbon emissions in China. This study uses the superefficiency EBM-DEA model considering undesirable outputs to estimate the transportation sector carbon dioxide emission efficiency (TSCDEE) for 30 provinces in China from 2012 to 2022. The Tobit model is used to analyze the influencing factors of TSCDEE and the heterogeneous characteristics of the influencing factors across regions. The results indicate that the mean value of efficiency in Chinese provinces is 0.709. The overall TSCDEE in China shows a fluctuating upward trend, with the carbon emission efficiency higher in coastal areas but lower in the Southwest and Northeast. This study shows that factors such as freight turnover level, transportation infrastructure level, and technological progress have significant positive impacts on TSCDEE. In contrast, population mobility has a significant negative effect on TSCDEE. Based on the above results, this study proposes specific measures such as optimizing travel modes, improving infrastructure construction, increasing freight turnover, and promoting technological progress. This study also considers the differences between eight regions and offers targeted suggestions. These findings provide a reference for achieving green and low-carbon development in the transportation sector.